2024
DOI: 10.1590/2317-4889202420230063
|View full text |Cite
|
Sign up to set email alerts
|

The hidden passive margins from the birth of SW Gondwana

Lucas Veríssimo Warren,
Victoria Penzo,
María Julia Arrouy
et al.

Abstract: The final consolidation of southwestern Gondwana during the Ediacaran-Cambrian resulted in the formation of a large landmass originally surrounded by the newborn Panthalassic Ocean. The Río de la Plata Craton is one of the last pieces that complete the geotectonic puzzle along the austral part of this supercontinent. However, the sedimentary record corresponding to the interval between the consolidation of SW Gondwana until the initial deposition in a large Ordovician cratonic basin is apparently missing. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…In previous geochronological studies [63], sandstones showed a dominant concentration of Paleoproterozoic detrital zircons, accompanied by other populations of Archean to lowermost Paleoproterozoic and Mesoproterozoic ages [4]. Archean detrital zircons of this succession indicate a source of detritus from the Nico Perez Terrane (Uruguay), which is closer to Tandilia up to the present [64]. In addition, the lack of Neoproterozoic detrital zircons confirms the deposition in a cratonic margin, probably in an epeiric sea deepening to the east and south [4].…”
Section: Detrital Components: Origin and Evolutionmentioning
confidence: 60%
See 3 more Smart Citations
“…In previous geochronological studies [63], sandstones showed a dominant concentration of Paleoproterozoic detrital zircons, accompanied by other populations of Archean to lowermost Paleoproterozoic and Mesoproterozoic ages [4]. Archean detrital zircons of this succession indicate a source of detritus from the Nico Perez Terrane (Uruguay), which is closer to Tandilia up to the present [64]. In addition, the lack of Neoproterozoic detrital zircons confirms the deposition in a cratonic margin, probably in an epeiric sea deepening to the east and south [4].…”
Section: Detrital Components: Origin and Evolutionmentioning
confidence: 60%
“…Geochronological data based on mineralogical, geochemical, and geochronology of detrital zircons, coupled with robust stratigraphic and sedimentologic background, support that this unit keeps more tectono-sedimentary affinity with Paleozoic sedimentary rocks of the Mar del Plata area (SE of Tandilia System) than the Neoproterozoic Sierras Bayas Group (NW Tandilia System, Figure 1). In addition, the absence of any metamorphism and deformation related to the Brazilian cycle and shallow marine deposition strongly suggest that the paleogeography and physiography of the original southernmost continental platform of Gondwana were similar in the latest Ediacaran and in the Paleozoic [64] (Figure 12).…”
Section: Compositional Variations In Sw-gondwana (Sequences VII and V...mentioning
confidence: 99%
See 2 more Smart Citations